(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: The purpose of the study was to assess the medication adherence among patients with mental illness. Methods: The present study adopted descriptive non experimental research design. A total of 70 patients with mental illness were recruited using a convenience sampling technique. In this study, the data was obtained through interview technique on demographic variables, medication related variables and medication adherence scale from samples who were satisfied the inclusion criteria. Results: The study finding revealed that 20 (28.5%) patients had low medication adherence, 27 (38.5%) patients had medium medication adherence and 23 (33%) patients had high medication adherence level. There was a significant association between the level of medication adherence and the residence at the level of p<0.05 Conclusion: Improving the support system by getting the family involved in the management of the patient, empowering them with educational, behavioral techniques and improving living condition of patient will improve medication adherence.